Unmet Need For Family Planning And Associated Factors Among Currently Married Women Of Reproductive Age In Bungus City Padang - yollanda dwi santi violentina (Andragogi Kesehatan BBPK Makassar, 2022)
Unmet needs for family planning is a problem in family planning (KB) that needs special attention. The highest unmet need for family planning in Padang City is in Bungus District, with a percentage of 29.6%, while the national target is 6.5%. The purpose of this study was to analyze the factors that influence the unmet need for family planning in the Bungus Padang area. This study uses a qualitative descriptive research method which was carried out in March-May 2019 at the Bungus Health Center, Bungus BKKBN Representative Office, and the Bungus Health Center working area with samples taken using the principles of appropriateness and adequacy, namely the Head of the MCH/KB Responsible Division, PLKB, two midwifes, and five women of childbearing age. The results of the analysis show that there are obstacles that cause the high unmet need for family planning, namely the lack of human resources, lack of socialization, lack of the role of midwives, religious factors, and the husband's support. The conclusion is that the unmet need for family planning in the Bungus area is still high due to various factors. The process of socialization and implementation needs improvement in order to increase community activity. Keywords: Unmet need for family planning, husband’s support, Role of Midwife